2023
DOI: 10.3390/molecules28124575
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-Mediated Reduction of Carboxamides to Amines with Borane–Ammonia

Abstract: In this study, the successful titanium tetrachloride-catalyzed reduction of aldehydes, ketones, carboxylic acids, and nitriles with borane–ammonia was extended to the reduction (deoxygenation) of a variety of aromatic and aliphatic pri-, sec- and tert-carboxamides, by changing the stoichiometry of the catalyst and reductant. The corresponding amines were isolated in good to excellent yields, following a simple acid–base workup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We have recently reported the effect of catalytic titanium tetrachloride (TiCl 4 ) for the borane-amine mediated reduction of ketones, 29 acids, 30 amides, 31 and nitriles, 32 deoxygenation of esters to ethers 33 and deoxyhalogenation of carbonyl compounds. 34 During these projects, we undertook a systematic evaluation of the catalytic ability of several metal halides and established that the reaction depended on the Lewis acidity of these halides and TiCl 4 is a critical and superior catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported the effect of catalytic titanium tetrachloride (TiCl 4 ) for the borane-amine mediated reduction of ketones, 29 acids, 30 amides, 31 and nitriles, 32 deoxygenation of esters to ethers 33 and deoxyhalogenation of carbonyl compounds. 34 During these projects, we undertook a systematic evaluation of the catalytic ability of several metal halides and established that the reaction depended on the Lewis acidity of these halides and TiCl 4 is a critical and superior catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…33 We subsequently demonstrated that TiCl 4activated carboxamides can be conveniently reduced to the corresponding amines with 1a. 34 Systematic extension of this process to reduce carboxylic esters to alcohols has now led to a novel catalyst-dependent deoxygenative reduction to ethers or to alcohols (Scheme 1v).…”
mentioning
confidence: 99%
“…During these projects, ketones or acids were selectively reduced in the presence of esters, which is not surprising given the fact that esters are poor substrates for reduction with BTHF or BMS . We subsequently demonstrated that TiCl 4 -activated carboxamides can be conveniently reduced to the corresponding amines with 1a . Systematic extension of this process to reduce carboxylic esters to alcohols has now led to a novel catalyst-dependent deoxygenative reduction to ethers or to alcohols (Scheme v).…”
mentioning
confidence: 99%
“…4 Very recently, Ramachandran and co-workers reduced nitriles, amides and carboxylic acids using AB and TiCl 4 . 5–7 Among the various B–N dehydrogenated species, 8 aminodiborane (μ-NH 2 B 2 H 5 , ADB) has received recent interest in organic and inorganic syntheses. 9–14 ADB is a strained molecule, which is sensitive to moisture and air.…”
mentioning
confidence: 99%